Creative Selection between Emending and Forming Medieval Memory - Scholz, Sebastian; Schwedler, Gerald; Scholz, Sebastian; Schwedler, Gerald (Berlin/Boston De Gruyter, 2021)
How can it be, that only as much happens as fits into the newspaper the next day? (K. Valentin). Information of the past has to be organised, arranged and selected. The process of selection must be seen as the fundamental moment of making History. This book shows selection as creative act. With the richness of early medieval material it can be demonstrated that creative selection was omnipresent and took place even in unexpected text genres.
English
Keywords: Ancient history: to c 500 CE; Classical history / classical civilisation; Medieval history; early middle ages; damnatio memoriae; historiography; memory